Subacute Drug-Eluting Stent Thrombosis Caused by Stent Underexpansion: Evaluation by Optical Coherence Tomography. (23rd February 2011) - Martín-Reyes, Roberto; Jiménez-Valero, Santiago; Navarro, Felipe; Moreno, Raúl
Abstract : We present the case report of a patient presenting with ST segment elevation myocardial infarction due to a subacute drug-eluting stent trombosis within the proximal segment of the left circumflex artery (LCX). Six days before a total chronic occlusion was treated at the mid segment of the LCX by overlapping two drug-eluting stents. Optical coherence tomography (OCT) was helpful to demonstrate stent underexpansion of the overlaping segment as the main mechanism of early stent thrombosis. This case is illustrative about the potential role of OCT to identify the mechanisms of ST and thus guiding the PCI procedure. Moreover, our case shows the capability of the Imagewire to cross a severe stenosis due to stent underexpansion that could not be crossed by the IVUS catheter.